A Literature Review on the Effectiveness of Problem-Based Learning in Enhancing Biology Students’ Problem Solving Skills and Learning Outcomes - Risalatul Muawanah; Ananda Fitri Ar Ridho; Nuril Badriyah; Fatimatus Zahro; Yamin Yamin (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to review the effectiveness of the Problem-Based Learning (PBL) learning model in improving students' problem-solving skills and learning outcomes in Biology. This study was conducted using a literature review method of relevant national and international articles. Data sources were obtained through a Google Scholar search with the keywords